Analysis of Sustainability and Sharia Compliance in Fintech and E-Commerce Business Services in Indonesia - Annisa Putri Maharani; Anggun Okta Fitri; Muhammad Iqbal Fasa (Syamilah Publishing, 2025)
This research was conducted based on the economic development sector in Indonesia. Interaction between consumers and producers is now made more active and efficient, with the existence of e-commerce services and carried out digitally, there is no need to bring two parties together. not only in terms of transactions, but also in the financial services sector, where there has also been a transformation from initially transactions carried out using paper money, to now switching to using digital money with the presence of financial technology (fintech), even sharia-based ones. So with the events in these brackets, a problem formulation was created regarding how to study recording analysis and fintech as well as opportunities in sharia business in Indonesia. This research is a study of the literature in analytical descriptive type. Discusses e-commerce and Fintech from various reference sources which are collected and used as descriptions to facilitate the analysis process. The results conclude that the transformation of e-commerce and Fintech and its overall application are very beneficial for both consumers and producers, but there are still shortcomings such as fraud, protection of consumers' personal data, and unsuitable ordered goods. If you look at the competition with conventional financial institutions, of course sharia fintech still needs quite a long time, especially now that it is still in the minority so its use is not as widespread as conventional institutions.